Electrical furnace for producing carbide coatings using the thermoreactive deposition/diffusion technique (2011)
In this work, the design of an electrical furnace for producing transition metal-based hard coatings using the thermo-reactive deposition and diffusion (TRD) technique is described. Performance of the system was tested through production of vanadium carbide (VC) and niobium carbide (NbC) coatings on steel AISI D2. X-ray diffraction (XRD) and optical microscopy techniques were used to study phase formation and microstructure, respectively. Hardness was determined by using Knoop microhardness measurements. XRD results showed the presence of VC and NbC, and as MEB results clearly show, the formation of regular thickness coatings. The results obtained allow for assessing that the designed and built furnace fulfills the requirements of the TRD technique for obtaining different types of hard coatings.